A critical evaluation of the understanding of critical thinking by school teachers: The case of Hong Kong. (April 2016) - Mok, Francis KT; Yuen, Timothy WW
There is a strong belief that critical thinking should be cultivated in schools. But it is not clear how critical thinking is understood by front-line teachers who are given the responsibility of training critical thinkers. Based on a study conducted in Hong Kong, we found that some school teachers were in favor of a "positive" image of critical thinker who is knowledgeable, prudent, being critical to the critics who are ready to criticize, and being constructive after making criticisms. We try to argue that such a positive portrayal, although uncontroversial from a detached point of view, may not be adequate in the context of Hong Kong where a critical stance toward power holders and established interests is badly needed. Without paying due attention to the "aporetic" dimension, such understanding of critical thinking would make it difficult for students to adopt a critical stance to the prevailing cultural beliefs, social values, political institutions, or economic ideologies that merit the greatest attention.